The mortality of men in the Rhondda Fach, 1950–1970. Issue 1 (February 1979) - Cochrane, A L; Haley, T J; Moore, F; Hole, D
Abstract : A more detailed analysis of material from the 20-year follow-up of men in the Rhondda Fach confirms the similarity between the Standardised Mortality Ratios (SMRs) of miners and exminers with radiological categories 0, 1, 2, 3 and A (120.3, 116.5, 119.0, 115.7, and 120.1 respectively) as well as the difference between these SMRs and that of the non-moners (98.7). The specific death rates show a raised SMR for bronchitis and other respiratory diseases excluding pneumoconiosis for all categories including category 0, but little difference between those for category 0 and those for simple pneumoconiosis. The SMRs for ischaemic heart disease and other circulatory diseases for categories A, B and C combined are lower than those for simple pneumoconiosis and category 0 (84.2 and 85.0, compared with 109.8 and 121.8 for simple pneumoconiosis, and 117.5 and 114.6 for category 0). Fortunately the SMR for leukaemia is low. A comparison between the survival rates of men aged 55-64 in Leigh, Lancashire and those in the Rhondda Fach suggests that nonminers in the two areas have similar survival rates while the survival rates for category 0 and simple pneumoconiosis are lower in the Rhondda Fach.